Legalitas Pencatatan Perkawinan Melalui Penetapan Isbat Nikah - Lubis, Akma Qamariah; Tanjung, Dhiauddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Itsbat of marriage is an endorsement of the assignment process, which has been held on the basis of Islamic jurisprudence, but not recorded at KUA. The goal of itsbat is to get a marriage license deed as evidence of legitimate marriage in accordance with the legislation in force in Indonesia, as provided for in article 2 paragraph (1) and (2) of law No. 1 of the year 1974 and article 7 paragraph (1), (2) and (3) Compilation Of Islamic Law. Itsbat matter of marriage (endorsement of marriage) may be filed in voluntair (the petition) and filed in kontentius (the suit) to the Court. Basic consideration of judges in giving the setting of itsbat marriage in a religious Court of which namely: 1) Legal standing (legal position) the applicant to litigate itsbat marriage in a religious court based on the provisions of article 7 paragraph (4) KHI, 2) Posita (facts and legal facts of the incident), 3) witnesses and evidence in the trial, as well as 4) the reasons for filing the itsbat marriage. This study aims to determine the legality of marriage registration through marriage isbat. This research uses the type of normative research. The results of the study indicate that the legitimacy of marriage registration through the determination of isbat.